The Implementation of Productive Waqf in Pesantren Gontor - Andi Triyawan; Nursilah Ahmad; Asmaddy Haris; Noradilah Abdul Hadi (Fakulti Ekonomi dan Muamalat, Universiti Sains Islam Malaysia, 2024)
This paper discusses productive waqf and the uniqueness of the application of productive waqf management in a pesantren (Islamic boarding school). Furthermore, the standardisation of the law used in the implementation of the productive waqf, which includes al-Qur'an, Hadits, fiqh rules, and aqwal al-'ulama, must be examined in order to reach a conclusion on the implementation status. There are many unique things to analyze in the implementation, such as the use of the institution fund, which is oriented to develop cash waqf, and the exictence of the waqf board, which becomes the highest decision maker. Because all of the pesantren's assets become waqf property, the highest leader is no longer on the foundation but on the waqf board.